2022
DOI: 10.1002/mgg3.1939
|View full text |Cite
|
Sign up to set email alerts
|

Yield of array‐CGH analysis in Tunisian children with autism spectrum disorder

Abstract: Background Autism spectrum disorder (ASD) is a neurodevelopmental disorder with strong genetic underpinnings. Microarray‐based comparative genomic hybridization (aCGH) technology has been proposed as a first‐level test in the genetic diagnosis of ASD and of neurodevelopmental disorders in general. Methods We performed aCGH on 98 Tunisian children (83 boys and 15 girls) diagnosed with ASD according to DSM‐IV criteria. Results “Pathogenic” or “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 106 publications
2
3
0
Order By: Relevance
“…In this study, we used a previously validated and trained CMA platform [ 35 , 36 ] for the screening of apparently (under clinical geneticists’ supervision) non-syndromic ASD individuals, which allowed us to segregate up to 87% of individuals in the cohort or to classify CNVs in approximately 75% of the patients showing CNVs (see Figure 3 ). These rates are similar to or even higher than those previously published for global ASD in our country or nearby [ 19 , 23 , 24 , 30 , 32 , 34 ]. Regarding the quick segregation mentioned before, we were able to establish a statistically significant relationship between the size of the CNVs and their clinical classification (under ACM/AMP criteria) in primary ASD patients.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study, we used a previously validated and trained CMA platform [ 35 , 36 ] for the screening of apparently (under clinical geneticists’ supervision) non-syndromic ASD individuals, which allowed us to segregate up to 87% of individuals in the cohort or to classify CNVs in approximately 75% of the patients showing CNVs (see Figure 3 ). These rates are similar to or even higher than those previously published for global ASD in our country or nearby [ 19 , 23 , 24 , 30 , 32 , 34 ]. Regarding the quick segregation mentioned before, we were able to establish a statistically significant relationship between the size of the CNVs and their clinical classification (under ACM/AMP criteria) in primary ASD patients.…”
Section: Discussionsupporting
confidence: 90%
“…We found 28 cases carrying P/LP CNVs associated with apparently primary ASD (approximately 13% of the subjects) that were similar to previous reports in global ASD individuals [ 20 , 30 , 34 ] in the literature and slightly higher than other studies reported in our country [ 19 , 22 , 23 ], but is difficult to compare because many of the studies do not segregate between isolated and non-isolated ASD subjects. We also observed VUS variants in 26 of 212 cases (12.26%).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These studies concentrate on various aspects of ASD in Tunisia, thoroughly investigating and analyzing multiple dimensions, including biology, cognition, psychosocial factors, and immunology. The research explores the impact of gut microbiota ( 59 ) and genomic variations ( 60 ) on patients, elucidating challenges in cognitive abilities ( 61 ), emotional recognition ( 62 ), and familial issues ( 63 ). Furthermore, investigations into immunological characteristics contribute to comprehending the pathological mechanisms of autism ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…CNVs were found in 90% of the 333 CMAs analysed, and 38 CNVs interpreted as pathogenic were detected in 35 cases with ASD, resulting in a diagnostic yield of 10%, lower than the diagnostic rate for the whole cohort (17%), but within the range of 8 to 22% cited in the literature for other ASD cohorts 16,70,[73][74][75][76][77][78][79][80][81][82][83][84][85] . And without the ASD cases, the diagnostic rate of the cohort increases to 20%.…”
Section: Asd Casesmentioning
confidence: 99%